PENGGUNAAN MEDIA LINGKUNGAN UNTUK MENINGKATKAN AKTIVITAS DAN KEMAMPUAN MENULIS PUISI PADA SISWA KELAS VIII SMPN 13 BANDAR LAMPUNG TP 2018/2019 - Pilu Minasari (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
The choice of this research topic was due to the low achievement of learning Indonesian, especially the students' ability to write poetry. The purpose of this study was to describe the increase in the ability to write poetry using environmental media in class VIII students of SMPN 13 Bandar Lampung. The method used in this research is Classroom Action Research. The research subjects were students of class VIII Semester 1 SMPN 13 Bandar Lampung for the 2018/2019 academic year, totaling 31 students. Data were obtained from observer observation sheet notes on the learning process planned by the researcher, learning activity observation sheets, and test sheets to determine learning achievement. Based on the findings and discussion results for 3 cycles, learning activities from cycle 1 to cycle 2 increased 18.5%, cycle 2 to cycle 3 increased 19%. Meanwhile, learning achievement from cycle 1 to cycle 2 increased by 15%, cycle 2 to cycle 3 increased by 26%, and observations of observers who partnered with researchers showed that the average criteria were good. Thus, the use of environmental media can increase the activity and ability to write poetry for eighth grade students of SMPN 13 Bandar Lampung semester 1 in Bandar Lampung TP 2018/2019.